Modifier and modification method of coral aggregate and modified coral aggregate

Through the dual treatment of composite powder rust inhibitor and wrapper, the problem of improving the strength and corrosion resistance of coral aggregates is solved, and the effects of increasing cylinder pressure strength, reducing crushing indicators and reducing free chloride ion content are achieved, which is extended. The service life of concrete structures.

CN119143415AActive Publication Date: 2024-12-17TSINGHUA UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411322169.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-17
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the cylinder pressure strength, crushing index and reduce the free chloride ion content of coral aggregates, and a single cement modification treatment cannot effectively immerse the inside of coral aggregates.

Method used

Compound powder rust inhibitors, including inorganic salts, carboxylic acid compounds and inorganic nanomaterials, are used to form an inclusion layer through soaking and embedding treatment, which enhances the compactness and corrosion resistance of the aggregate.

Benefits of technology

It significantly improves the cylinder pressure strength of coral aggregates, reduces crushing indicators and free chloride ion content, extends the service life of concrete structures, and improves the strength and corrosion resistance of aggregates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143415A_ABST
    Figure CN119143415A_ABST
Patent Text Reader

Abstract

The invention provides a coral aggregate modifier, a modification method and a modified coral aggregate. The modifier at least comprises a composite powder corrosion inhibitor, and the composite powder corrosion inhibitor comprises an inorganic salt, a carboxylic acid compound and an inorganic nano-material. The modification method comprises the following steps: soaking the coral aggregate in a solution of a composite powder corrosion inhibitor, wrapping with a wrapping agent, and curing to obtain the modified coral aggregate. According to the invention, the cylinder compressive strength and crushing index of the coral aggregate can be improved, and the content of free chloride ions can be controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coral aggregate modifier, a modification method and modified coral aggregate, and belongs to the technical field of building materials. Background Art

[0002] With the active advancement of marine engineering construction, concrete, as the basic material in the marine engineering construction process, has also received widespread attention and attention due to the availability of raw materials and its service performance in harsh environments.

[0003] The volume ratio of aggregate in concrete is about 70%-80%. In the construction of offshore islands and reefs, the demand for sand and gravel aggregates, as an important component, is huge. If the aggregates are transported by ship shipping, the cost of the project will increase significantly. In order to meet the needs of the rapid development of marine engineering construction, it is urgent to find alternative materials that meet the requirements of the project. Making full use of marine resources and taking into account the protection of the marine ecological environment can greatly reduce the pre-construction and post-maintenance costs of island and reef construction projects. Therefore, under the premise of not destroying the original ecological environment, using coral gravel on the island as aggregate for concrete can effectively reduce the construction cost of island and reef projects and speed up the construction progress.

[0004] Unlike ordinary lightweight aggregates, coral aggregate is a porous material with basic characteristics such as light weight, porosity, high water absorption, and low strength. Scholars have focused their research on single modification to enhance the performance of coral aggregate. The main methods are: inorganic modification, organic modification, and biological modification. For example, soaking coral aggregate in water glass solution, soaking coral aggregate in PVA (polyvinyl alcohol) solution, and using bacterial culture cylinders to culture microorganisms in coral aggregate. However, there are three main indicators for measuring the performance of coral aggregates: cylinder compression strength, crushing index, and free chloride ion content. At present, the main method of modifying and improving coral aggregates is cement coating slurry, but a single cement modification cannot completely penetrate into the interior of the coral aggregate, and cannot effectively reduce the free chloride ion content of the coral aggregate.

[0005] CN109354431B discloses a method for adding rust inhibitors to improve the durability of coral concrete structures. The method mixes the rust inhibitor with seawater and pours it into crushed coral aggregate for pre-absorption treatment. According to the characteristics of coral aggregate "absorbing water and returning water", the rust inhibitor inside the coral aggregate is released, thereby increasing the resistance to the movement of chloride ions. CN110981255B discloses a method for reinforcing porous coral aggregates. The method uses a water glass solution and a calcium ion solution to treat coral aggregates, uses chemical reactions to generate calcium silicate precipitation to fill the pores, and uses a reinforcing agent slurry to further improve the density and strength, and finally obtains modified coral aggregates through maintenance. CN111943546A discloses a coral aggregate and a low-cost modification method thereof. The method soaks the coral aggregate in a slag solution and stirs the water glass solution, effectively reducing its porosity and water absorption through corresponding chemical reactions, thereby improving the mechanical properties. Huang Long explored the application of nanomaterials in coral aggregate concrete, using nano-SiO 2 、Nano-TiO 2 and nano-CaCO 3 A suspension of three nanomaterials was prepared and used to soak the coral aggregate in a vacuum environment to fill its pores (Huang Long. Experimental study on basic mechanical properties and impermeability of modified coral aggregate concrete [D], 2022.).

[0006] Most of the rust inhibitors used in the prior art are liquid rust inhibitors, and most of them have relatively simple ingredients, which makes it difficult to simultaneously fill the pores of the aggregate and reduce the free chloride ion content. In addition, the modification methods in the prior art make it difficult to simultaneously improve the cylinder compressive strength, crushing index and free chloride ion content of coral aggregates. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a coral aggregate modifier, a coral aggregate modification method and a modified coral aggregate. The present invention can improve the cylinder compression strength and crushing index of the coral aggregate and control the free chloride ion content.

[0008] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a modifier for coral aggregate, which at least includes: a composite powder rust inhibitor, which includes: 30-40% of inorganic salt, 10-30% of carboxylic acid compound and 20-35% of inorganic nanomaterial based on the total weight of the composite powder rust inhibitor as 100%; wherein the carboxylic acid compound includes one or a combination of aminocarboxylate and unsaturated carboxylic acid.

[0009] According to a specific embodiment of the present invention, preferably, the inorganic salt includes zinc sulfate and / or calcium sulfate, etc. More preferably, the inorganic salt includes a combination of zinc sulfate and calcium sulfate, and based on the total weight of the composite powder rust inhibitor as 100%, the content of zinc sulfate is 15-20%, and the content of calcium sulfate is 15-25%.

[0010] According to a specific embodiment of the present invention, preferably, the aminocarboxylate includes aminoacetate and the like, and the unsaturated carboxylic acid includes acrylic acid and the like.

[0011] According to a specific embodiment of the present invention, preferably, the inorganic nanomaterial includes nano titanium dioxide and / or nano zinc oxide.

[0012] According to a specific embodiment of the present invention, preferably, based on the total weight of the composite powder rust inhibitor being 100%, it further comprises: 5-10% of a stabilizer, wherein the stabilizer comprises a surfactant.

[0013] According to a specific embodiment of the present invention, preferably, based on the total weight of the composite powder rust inhibitor being 100%, it further comprises: 5-10% of a pH value regulator.

[0014] According to a specific embodiment of the present invention, preferably, the coral aggregate modifier further comprises: a coating agent, and the coating agent comprises: cement and water.

[0015] It should be noted that the composite powder rust inhibitor and the encapsulating agent of the present invention can be stored separately. When modifying the coral aggregate, the composite powder rust inhibitor and the encapsulating agent can be used step by step to modify the coral aggregate according to the modification method described below.

[0016] According to a specific embodiment of the present invention, preferably, the weight ratio of the composite powder rust inhibitor to the encapsulating agent is (0.2-0.4):1.

[0017] According to a specific embodiment of the present invention, preferably, the cement includes one or a combination of ordinary cement, special cement and corrosion-resistant cement.

[0018] According to a specific embodiment of the present invention, preferably, the encapsulating agent further comprises: a cementitious material; and a weight ratio of the cementitious material to the cement is (0.2-0.4):1.

[0019] According to a specific embodiment of the present invention, preferably, the weight ratio of water in the encapsulating agent to the total amount of cement and optionally included cementitious materials (ie, water-cement / cement ratio) is (0.2-0.6):1.

[0020] According to a specific embodiment of the present invention, preferably, the cementitious material includes one or a combination of fly ash, blast furnace slag powder, recycled powder, coral sand powder, quartz sand powder and basalt powder.

[0021] According to a specific embodiment of the present invention, preferably, the density of the encapsulating agent is 3.0-3.5 g / cm 3 .

[0022] A second aspect of the present invention provides a method for modifying coral aggregates, the method using the above-mentioned coral aggregate modifier, comprising the following steps:

[0023] (1) soaking the coral aggregate in a solution of the composite powder rust inhibitor to obtain the coral aggregate soaked in the composite powder rust inhibitor;

[0024] (2) using a coating agent to coat the coral aggregate after being impregnated with the composite powder rust inhibitor to form a coating agent layer, thereby obtaining a coral aggregate having a coating agent layer;

[0025] (3) Curing the coral aggregate with the coating layer to obtain modified coral aggregate.

[0026] According to a specific embodiment of the present invention, preferably, the particle size of the coral aggregate is 5-20 mm.

[0027] According to a specific embodiment of the present invention, preferably, the mass fraction of the composite powder rust inhibitor in the solution of the composite powder rust inhibitor is 3-50%.

[0028] According to a specific embodiment of the present invention, preferably, the pH value of the solution of the composite powder rust inhibitor is 9-12.

[0029] According to a specific embodiment of the present invention, preferably, the volume ratio of the solution of the composite powder rust inhibitor to the coral aggregate is (1-3):1.

[0030] According to a specific embodiment of the present invention, preferably, the soaking time is 3-5 hours.

[0031] According to a specific embodiment of the present invention, preferably, the coral aggregate impregnated with the composite powder rust inhibitor is coated with a coating agent by spraying or immersing under vibration conditions, so that the coating agent is coated on the surface of the coral aggregate and filled in the pores of the coral aggregate, forming a coating agent layer on the surface of the coral aggregate.

[0032] According to a specific embodiment of the present invention, preferably, the thickness of the wrapping agent layer is 0.05-0.2 cm.

[0033] According to a specific embodiment of the present invention, preferably, the curing includes standard curing, carbonization curing or steam curing. Specifically, the conditions of the standard curing include: curing for 28 days in an environment with a temperature of 20°C ± 3°C and a relative humidity of 90% or more; the conditions of the carbonization curing include: curing for 1-28 days in an environment with a carbon dioxide concentration of 20% ± 3%, a relative humidity of 70% ± 5%, and a temperature of 20°C ± 2°C; the conditions of the steam curing include: curing for 1-28 days in an environment with a temperature of 50-80°C and a humidity of 90% or more.

[0034] The third aspect of the present invention provides a modified coral aggregate, which is prepared by the above-mentioned coral aggregate modification method.

[0035] The present invention has at least the following beneficial effects:

[0036] The present invention soaks coral aggregates in a solution of a composite powder rust inhibitor for a long soaking time. The inorganic and organic components in the composite powder rust inhibitor fully penetrate the interior of the aggregate and produce a synergistic effect to adsorb and fill the aggregate. It can adsorb chloride ions in the aggregate, and then solidify the chloride ions to reduce the free chloride ion content of the aggregate. At the same time, it can fill the pores inside the aggregate, increase the pore density of the aggregate, and improve the strength of the aggregate. After the coral aggregate is soaked in the rust inhibitor, the present invention uses a coating agent containing cement to treat the coral aggregate, fill the surface pores of the aggregate, and form a coating agent layer on the surface of the aggregate to further enhance the density of the aggregate. Afterwards, the present invention maintains the coral aggregate with the coating agent layer to fully hydrate the cement, such as generating hydrated calcium silicate, which can significantly improve the strength and durability of the aggregate. The present invention adopts the method of first impregnating the rust inhibitor and then using the coating agent. This composite modification method comprehensively improves the performance of the coral aggregate, so that the modified coral aggregate of the present invention has improved cylinder compression strength, reduced crushing index, reduced free chloride ion content, improved strength and corrosion resistance of the aggregate, and extended the service life of the concrete structure. In addition, the modified coral aggregate of the present invention also has the advantages of being non-toxic and harmless, and having a simple preparation process. The present invention provides a new method for the application of coral aggregate concrete and increases the application range of coral aggregate concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic flow chart of the modification method of coral aggregate in a specific embodiment of the present invention.

[0038] Figure 2 This is an optical image of the modified coral aggregate of Example 1.

[0039] Figure 3 This is an optical image of the modified coral aggregate of Comparative Example 1.

[0040] Figure 4 This is an optical image of the modified coral aggregate of Comparative Example 2.

[0041] Figure 5 Optical image of unmodified coral aggregate. DETAILED DESCRIPTION

[0042] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0043] According to a specific embodiment of the first aspect of the present invention, the present invention provides a modifier for coral aggregate, which at least includes: a composite powder rust inhibitor, which includes: 30-40% of inorganic salt, 10-30% of carboxylic acid compound and 20-35% of inorganic nanomaterial based on the total weight of the composite powder rust inhibitor as 100%; wherein the carboxylic acid compound includes one or more of aminocarboxylate and unsaturated carboxylic acid. Combination.

[0044] In some embodiments, the inorganic salt comprises zinc sulfate (ZnSO 4 ) and / or calcium sulfate (CaSO 4 ) etc. Preferably, the inorganic salt comprises a combination of zinc sulfate and calcium sulfate, and based on the total weight of the composite powder rust inhibitor being 100%, the content of zinc sulfate is 15-20%, and the content of calcium sulfate is 15-25%.

[0045] In some embodiments, the aminocarboxylate includes aminoacetate, etc., and the unsaturated carboxylic acid includes acrylic acid, etc. Specifically, the aminoacetate may include sodium aminoacetate, etc.

[0046] In some embodiments, the inorganic nanomaterial includes nano titanium dioxide (TiO 2 ) and / or nano zinc oxide (ZnO), etc. Preferably, the particle size of the inorganic nano material is 5-50nm.

[0047] In some embodiments, based on the total weight of the composite powder rust inhibitor being 100%, it further comprises: 5-10% of a stabilizer, wherein the stabilizer comprises a surfactant, and specifically, the stabilizer comprises one or a combination of anionic surfactants, cationic surfactants, and amphoteric surfactants.

[0048] In some embodiments, based on the total weight of the composite powder rust inhibitor being 100%, it further comprises: 5-10% of a pH value adjuster. Specifically, the pH value adjuster may include dilute sulfuric acid and / or sodium hydroxide.

[0049] The present invention has developed a composite powder rust inhibitor, in which the inorganic salt can react with chloride to reduce the corrosion of steel bars when used; the carboxylic acid compound can form a protective film on the coral aggregate to slow down the corrosion rate of the steel bars when used; the inorganic nanomaterial can improve the comprehensive performance of the rust inhibitor due to its high specific surface area and unique physical and chemical properties. The various components in the composite powder rust inhibitor can fully penetrate into the aggregate and produce a synergistic effect to adsorb and fill the aggregate.

[0050] In some embodiments, the coral aggregate modifier further comprises a coating agent, wherein the coating agent comprises cement and water.

[0051] In some embodiments, the weight ratio of the composite powder rust inhibitor to the encapsulating agent is (0.2-0.4):1, preferably 0.3:1.

[0052] In some embodiments, the cement includes one or a combination of ordinary cement, special cement, and corrosion-resistant cement, etc. The present invention does not impose any special restrictions on the specific substances / materials included in ordinary cement, special cement, and corrosion-resistant cement, and conventional cements in the art can be used, such as but not limited to silicate cement, aluminate cement, etc.

[0053] In some embodiments, the encapsulating agent further comprises: a cementitious material; the weight ratio of the cementitious material to the cement is (0.2-0.4):1, preferably 0.3:1.

[0054] In some embodiments, the weight ratio of water in the coating agent to the total amount of cement and optionally included cementitious materials (i.e., water: (cement + optionally included cementitious materials), also referred to as water-cement / cement ratio) is (0.2-0.6):1, preferably (0.4-0.5):1.

[0055] In some embodiments, the cementitious material includes one or a combination of fly ash, blast furnace slag powder, recycled powder, coral sand powder, quartz sand powder and basalt powder. The cementitious material is preferably basalt powder or coral sand powder, which is easier to fill the pores of the aggregate and wrap, thereby enhancing the strength of the aggregate. Preferably, the particle size of the cementitious material is 60 μm-100 μm.

[0056] In some embodiments, the density of the encapsulant is 3.0-3.5 g / cm 3 , preferably 3.3 g / cm 3 .

[0057] The invention controls the formula of the coating agent and the water-cement / binder ratio, so that the coating agent has good fluidity and uniformity, thereby being able to more fully and evenly fill the surface pores of the aggregate and form a uniform coating agent layer on the surface of the aggregate.

[0058] According to a specific embodiment of the second aspect of the present invention, the present invention provides a method for modifying coral aggregates, wherein the method uses the above-mentioned coral aggregate modifier, such as Figure 1 As shown, it includes the following steps:

[0059] (1) soaking the coral aggregate in a solution of the composite powder rust inhibitor to obtain the coral aggregate soaked in the composite powder rust inhibitor;

[0060] (2) using a coating agent to coat the coral aggregate after being impregnated with the composite powder rust inhibitor to form a coating agent layer, thereby obtaining a coral aggregate having a coating agent layer;

[0061] (3) Curing the coral aggregate with the coating layer to obtain modified coral aggregate.

[0062] In some embodiments, the particle size of the coral aggregate is 5-20 mm. Specifically, the coral aggregate can be made to meet the above particle size range by, for example, screening. The particle gradation of the coral aggregate can refer to the record in "Light Aggregate and Its Test Method" (GB / T 17431-2010). If the particle size of the coral aggregate does not meet the continuous gradation of 5-20 mm, aggregate crushing is required. In addition, before performing step (1), the coral aggregate can be dried at 100±5°C for 24-26 hours.

[0063] In some embodiments, the mass fraction of the composite powder rust inhibitor in the composite powder rust inhibitor solution is 3-50%.

[0064] In some embodiments, the pH value of the solution of the composite powder rust inhibitor is 9-12.

[0065] In some embodiments, the volume ratio of the solution of the composite powder rust inhibitor to the coral aggregate is (1-3):1.

[0066] In some embodiments, after the coral aggregate is placed in the composite powder rust inhibitor solution, it may be turned over for 8-10 minutes to allow the composite powder rust inhibitor solution to more fully enter the interior of the coral aggregate and remove the air inside the coral aggregate.

[0067] In some embodiments, the soaking time is 3-5 hours. The soaking temperature can be room temperature, generally 23±2° C. The soaking pressure can be normal pressure, or vacuum soaking can be performed under appropriate vacuum conditions.

[0068] In some embodiments, after the soaking is completed, the coral aggregate soaked with the composite powder rust inhibitor can be taken out of the solution and placed on a screen for shaking to drain the water. The shaking time on the screen can be 3-5 minutes. Draining the water is to make the coral aggregate reach a saturated surface dry state to avoid the rust inhibitor solution on the surface of the aggregate affecting the final judgment of the modification and strengthening.

[0069] In some embodiments, the coral aggregate soaked with the composite powder rust inhibitor is coated with a coating agent by spraying or soaking under vibration conditions, so that the coating agent is coated on the surface of the coral aggregate and fills the pores of the coral aggregate to form a coating agent layer on the surface of the coral aggregate. Preferably, the coating agent layer is sprayed to make the thickness of the coating agent layer more uniform.

[0070] In some embodiments, the soaking under vibration conditions specifically includes: placing the coral aggregate soaked with the composite powder rust inhibitor into the coating agent, stirring, vibrating, soaking, and filtering to obtain the coral aggregate with a coating agent layer. Specifically, the stirring time can be 3-5 minutes to ensure that the coral aggregate and the coating agent are in full contact. The vibration time can be 8-10 minutes, and the soaking time can be 15-30 minutes, so as to facilitate the coating agent to enter the pores of the aggregate for filling. A dense mesh can be used for the filtration to remove excess coating agent on the surface of the coral aggregate, and the filtration time can be 10-20 minutes, thereby avoiding the subsequent hardening of cement and causing aggregate bonding.

[0071] In some embodiments, the thickness of the wrapping agent layer is 0.05-0.2 cm.

[0072] In some embodiments, before the curing, the coral aggregate with the coating layer may be dried. The drying may be sun drying under natural conditions, and during the sun drying process, the coral aggregate is flattened as much as possible to ensure the uniformity of the coating layer on the aggregate surface.

[0073] In some embodiments, the curing includes standard curing, carbonization curing or steam curing. Specifically, the standard curing conditions include: curing for 28 days in an environment with a temperature of 20°C ± 3°C and a relative humidity of 90% or more; the carbonization curing conditions include: curing for 1-28 days in an environment with a carbon dioxide concentration of 20% ± 3%, a relative humidity of 70% ± 5%, and a temperature of 20°C ± 2°C; the steam curing conditions include: curing for 1-28 days in an environment with a temperature of 50-80°C and a humidity of 90% or more. The curing allows the cement to fully hydrate and develop, thereby improving the modification effect of the coral aggregate.

[0074] According to a specific embodiment of the third aspect of the present invention, the present invention provides a modified coral aggregate, which is prepared by the above-mentioned coral aggregate modification method.

[0075] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples and can of course be implemented with various modifications within the scope of the gist of the present invention.

[0076] Example 1

[0077] 1. Weigh coral aggregate with a particle size of 5-20 mm, so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5℃ for 24-26 hours;

[0078] 2. Add a composite powder rust inhibitor (whose composition is: 15% zinc sulfate, 25% calcium sulfate, 20% sodium aminoacetate, 30% nano titanium dioxide with a particle size of 5-50nm, 5% sodium dodecylbenzene sulfonate stabilizer, and 5% sodium hydroxide and / or dilute sulfuric acid as pH adjuster) into tap water and stir to prepare a 5% mass fraction composite powder rust inhibitor solution. The pH value of the composite powder rust inhibitor solution is 10. Put the coral aggregate into the composite powder rust inhibitor solution. The volume ratio of the composite powder rust inhibitor solution to the coral aggregate is 1.5:1. First, turn the coral aggregate for 8-10 minutes, and then soak it at room temperature and normal pressure for 3-5 hours. After the soaking, take the coral aggregate out of the solution, place it on a sieve and shake it for 3-5 minutes to drain the water, and obtain the coral aggregate soaked with the composite powder rust inhibitor;

[0079] 3. Ordinary Portland cement, basalt powder with a particle size of 60μm-100μm and water are mixed to prepare a coating agent. The weight ratio of the composite powder rust inhibitor to the coating agent is 0.3:1, the weight ratio of cement to basalt powder is 1:0.3, the water-cement / binder ratio of the coating agent is 0.4:1, and the density of the coating agent is 3.3g / cm 3 The coating agent is coated on the surface of the coral aggregate after being impregnated with the composite powder rust inhibitor by spraying and filled in the pores of the coral aggregate to form a coating agent layer, thereby obtaining a coral aggregate with a coating agent layer; the thickness of the coating agent layer is 0.1 cm;

[0080] 4. Place the coral aggregate with the coating layer under natural conditions to dry, and then perform standard curing, wherein the standard curing conditions include: curing for 28 days in an environment with a temperature of 20°C ± 3°C and a relative humidity of more than 90%, to obtain a modified coral aggregate. The optical image of the modified coral aggregate is as follows: Figure 2 The optical image of the unmodified coral aggregate is shown in Figure 5 shown.

[0081] Example 2

[0082] 1. Weigh coral aggregate with a particle size of 5-20 mm (the same as in Example 1), so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5°C for 24-26 hours;

[0083] 2. Add a composite powder rust inhibitor (whose composition is: 15% zinc sulfate, 25% calcium sulfate, 20% sodium aminoacetate, 30% nano titanium dioxide with a particle size of 5-50nm, 5% sodium dodecylbenzene sulfonate stabilizer, and 5% sodium hydroxide and / or dilute sulfuric acid as pH adjuster) into tap water and stir to prepare a 5% mass fraction composite powder rust inhibitor solution. The pH value of the composite powder rust inhibitor solution is 10. Put the coral aggregate into the composite powder rust inhibitor solution. The volume ratio of the composite powder rust inhibitor solution to the coral aggregate is 1.5:1. First, turn the coral aggregate for 8-10 minutes, and then soak it at room temperature and normal pressure for 3-5 hours. After the soaking, take the coral aggregate out of the solution, place it on a sieve and shake it for 3-5 minutes to drain the water, and obtain the coral aggregate soaked with the composite powder rust inhibitor;

[0084] 3. Ordinary Portland cement, basalt powder with a particle size of 60μm-100μm and water are mixed to prepare a coating agent. The weight ratio of the composite powder rust inhibitor to the coating agent is 0.3:1, the weight ratio of cement to basalt powder is 1:0.3, the water-cement / binder ratio of the coating agent is 0.4:1, and the density of the coating agent is 3.3g / cm 3 , put the coral aggregate soaked with the composite powder rust inhibitor into the coating agent, stir it with a stirrer for 3-5 minutes, vibrate it for 8-10 minutes, soak it for 15-30 minutes, and then filter it with a dense mesh for 10-20 minutes. After filtering, spread the aggregate flat to obtain a coral aggregate with a coating agent layer; the thickness of the coating agent layer is 0.1 cm;

[0085] 4. The coral aggregate with the coating layer is placed under natural conditions to dry, and then subjected to standard curing. The standard curing conditions include: curing for 28 days in an environment with a temperature of 20°C ± 3°C and a relative humidity of more than 90% to obtain a modified coral aggregate.

[0086] Example 3

[0087] 1. Weigh coral aggregate with a particle size of 5-20 mm (the same as in Example 1), so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5°C for 24-26 hours;

[0088] 2. Add a composite powder rust inhibitor (whose composition is: 15% zinc sulfate, 25% calcium sulfate, 20% sodium aminoacetate, 30% nano zinc oxide with a particle size of 5-50nm, 5% sodium dodecylbenzene sulfonate stabilizer, and 5% sodium hydroxide and / or dilute sulfuric acid as pH adjuster) into tap water and stir to prepare a 5% composite powder rust inhibitor solution. The pH value of the composite powder rust inhibitor solution is 10. Put the coral aggregate into the composite powder rust inhibitor solution. The volume ratio of the composite powder rust inhibitor solution to the coral aggregate is 1.5:1. First, turn the coral aggregate for 8-10 minutes, and then soak it at room temperature and normal pressure for 3-5 hours. After the soaking, take the coral aggregate out of the solution, place it on a sieve and shake it for 3-5 minutes to drain the water, and obtain the coral aggregate soaked with the composite powder rust inhibitor;

[0089] 3. Ordinary Portland cement, basalt powder with a particle size of 60μm-100μm and water are mixed to prepare a coating agent. The weight ratio of the composite powder rust inhibitor to the coating agent is 0.3:1, the weight ratio of cement to basalt powder is 1:0.3, the water-cement / binder ratio of the coating agent is 0.4:1, and the density of the coating agent is 3.3g / cm 3 The coating agent is coated on the surface of the coral aggregate after being impregnated with the composite powder rust inhibitor by spraying and filled in the pores of the coral aggregate to form a coating agent layer, thereby obtaining a coral aggregate with a coating agent layer; the thickness of the coating agent layer is 0.1 cm;

[0090] 4. The coral aggregate with the coating layer is placed under natural conditions to dry, and then carbonized and cured. The carbonized curing conditions include: curing for 28 days in an environment with a carbon dioxide concentration of 20%±3%, a relative humidity of 70%±5%, and a temperature of 20°C±2°C to obtain a modified coral aggregate.

[0091] Example 4

[0092] 1. Weigh coral aggregate with a particle size of 5-20 mm (the same as in Example 1), so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5°C for 24-26 hours;

[0093] 2. The composite powder rust inhibitor (whose composition is the same as that in Example 1) is added to tap water and stirred to prepare a solution of the composite powder rust inhibitor with a mass fraction of 5%. The pH value of the solution of the composite powder rust inhibitor is 10. The coral aggregate is placed in the solution of the composite powder rust inhibitor. The volume ratio of the solution of the composite powder rust inhibitor to the coral aggregate is 1.5:1. The coral aggregate is first turned over for 8-10 minutes, and then soaked at room temperature and normal pressure for 3-5 hours. After the soaking is completed, the coral aggregate is taken out from the solution, placed on a sieve and shaken for 3-5 minutes to drain the water, and the coral aggregate after the composite powder rust inhibitor is soaked is obtained;

[0094] 3. Ordinary Portland cement, coral sand powder with a particle size of 60μm-100μm and water are mixed to prepare a coating agent. The weight ratio of the composite powder rust inhibitor to the coating agent is 0.3:1, the weight ratio of cement to coral sand powder is 1:0.3, the water-cement / binder ratio of the coating agent is 0.4:1, and the density of the coating agent is 3.3g / cm 3 , put the coral aggregate soaked with the composite powder rust inhibitor into the coating agent, stir it with a stirrer for 3-5 minutes, vibrate it for 8-10 minutes, soak it for 15-30 minutes, and then filter it with a dense mesh for 10-20 minutes. After filtering, spread the aggregate flat to obtain a coral aggregate with a coating agent layer; the thickness of the coating agent layer is 0.1 cm;

[0095] 4. The coral aggregate with the coating layer is placed under natural conditions to dry, and then subjected to standard curing. The standard curing conditions include: curing for 28 days in an environment with a temperature of 20°C ± 3°C and a relative humidity of more than 90% to obtain a modified coral aggregate.

[0096] Comparative Example 1

[0097] 1. Weigh coral aggregate with a particle size of 5-20 mm (the same as in Example 1), so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5°C for 24-26 hours;

[0098] 2. The composite powder rust inhibitor (whose composition is the same as that in Example 1) is added to tap water and stirred to prepare a solution of the composite powder rust inhibitor with a mass fraction of 5%. The pH value of the solution of the composite powder rust inhibitor is 10. The coral aggregate is placed in the solution of the composite powder rust inhibitor. The volume ratio of the solution of the composite powder rust inhibitor to the coral aggregate is 1.5:1. The coral aggregate is first turned over for 8-10 minutes, and then soaked at room temperature and normal pressure for 3-5 hours. After the soaking is completed, the coral aggregate is taken out from the solution, placed on a sieve and shaken for 3-5 minutes to drain the water, and the coral aggregate after the composite powder rust inhibitor is soaked is obtained;

[0099] 3. Place the coral aggregate after absorbing the composite powder rust inhibitor under natural conditions and dry it to obtain modified coral aggregate. The optical image of the modified coral aggregate is as follows: Figure 3 shown.

[0100] Compared with Example 1, the steps of wrapping with a coating agent and curing are omitted in this comparative example.

[0101] Comparative Example 2

[0102] 1. Weigh coral aggregate with a particle size of 5-20 mm (the same as in Example 1), so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5°C for 24-26 hours;

[0103] 2. Prepare the same coating agent as in Example 1, and coat the surface of the coral aggregate with the coating agent and fill the pores of the coral aggregate with the coating agent by spraying to form a coating agent layer, thereby obtaining a coral aggregate having a coating agent layer; the thickness of the coating agent layer is 0.1 cm;

[0104] 3. The coral aggregate with the coating layer is placed under natural conditions to dry, and then subjected to standard curing, the standard curing conditions being the same as those in Example 1. The optical image of the modified coral aggregate is as follows: Figure 4 shown.

[0105] Compared with Example 1, the step of impregnating the composite powder rust inhibitor is omitted in this comparative example.

[0106] Comparative Example 3

[0107] This comparative example is basically the same as Example 1, except that: the rust inhibitor is different. The rust inhibitor in this comparative example is a calcium nitrite rust inhibitor. A calcium nitrite solution with a mass fraction of 5% is prepared, and the coral aggregate is placed in the calcium nitrite solution. The volume ratio of the calcium nitrite solution to the coral aggregate is 1.5:1; the other modification steps and conditions are the same as those in Example 1.

[0108] Comparative Example 4

[0109] This comparative example is basically the same as Example 1, except that: there is a difference in the composition of the composite powder rust inhibitor. The composition of the composite powder rust inhibitor in this comparative example is (in weight percentage): 35% sodium aminoacetate, 50% nano titanium dioxide with a particle size of 5-50nm, 10% stabilizer sodium dodecylbenzene sulfonate and 5% pH adjuster sodium hydroxide and / or dilute sulfuric acid. A solution of the composite powder rust inhibitor with a mass fraction of 5% is prepared, and the pH value of the solution of the composite powder rust inhibitor is 10; that is, the inorganic salt in the composite powder rust inhibitor of Example 1 is omitted in this comparative example; the other modification steps and conditions are the same as those in Example 1.

[0110] Comparative Example 5

[0111] This comparative example is basically the same as Example 1, except that: there is a difference in the composition of the composite powder rust inhibitor. The composition of the composite powder rust inhibitor in this comparative example is (in percentage by weight): 20% zinc sulfate, 30% calcium sulfate, 35% sodium aminoacetate, 10% sodium dodecylbenzene sulfonate stabilizer and 5% sodium hydroxide and / or dilute sulfuric acid as a pH adjuster. A solution of the composite powder rust inhibitor with a mass fraction of 5% is prepared, and the pH value of the solution of the composite powder rust inhibitor is 10; that is, the inorganic nanomaterial in the composite powder rust inhibitor of Example 1 is omitted in this comparative example; the other modification steps and conditions are the same as those in Example 1.

[0112] Comparative Example 6

[0113] This comparative example is basically the same as Example 1, except that: there is a difference in the composition of the composite powder rust inhibitor. The composition of the composite powder rust inhibitor in this comparative example is (in weight percentage): 20% zinc sulfate, 30% calcium sulfate, 35% nano titanium dioxide with a particle size of 5-50nm, 10% stabilizer sodium dodecylbenzene sulfonate and 5% pH adjuster sodium hydroxide and / or dilute sulfuric acid. A solution of the composite powder rust inhibitor with a mass fraction of 5% is prepared, and the pH value of the solution of the composite powder rust inhibitor is 10; that is, the aminocarboxylate in the composite powder rust inhibitor of Example 1 is omitted in this comparative example; the other modification steps and conditions are the same as those in Example 1.

[0114] Comparative Example 7

[0115] This comparative example is basically the same as Example 1, except that the basalt powder in the coating agent is omitted, the water-cement ratio of the coating agent is 0.4:1, and the density of the coating agent is 3.3 g / cm 3 ; Other modification steps and conditions are the same as in Example 1.

[0116] Comparative Example 8

[0117] 1. Weigh coral aggregate with a particle size of 5-20 mm, so that the particle size distribution of the coral aggregate meets the requirements of "Light Aggregate and Its Test Method" (GB / T 17431-2010), and dry the coral aggregate in an oven at 100±5℃ for 24-26 hours;

[0118] 2. The composite powder rust inhibitor (whose composition is the same as that of Example 1) and the wrapping agent (whose composition is the same as that of Example 1, the water-cement / binder ratio of the wrapping agent is 0.4:1, and the density is 3.3g / cm 3 ) are mixed in a weight ratio of 0.3:1 to obtain a composite modifier, coral aggregate is placed in the composite modifier, and stirred with a stirrer for 3-5 minutes, then vibrated for 8-10 minutes, and then soaked for 15-30 minutes, and then filtered with a dense mesh for 10-20 minutes. After the filtration is completed, the aggregate is spread flat to obtain a coral aggregate with a composite modifier layer; the thickness of the composite modifier layer is 0.1 cm;

[0119] 3. The coral aggregate with the composite modifier layer is placed under natural conditions to dry, and then subjected to standard curing. The standard curing conditions include: curing for 28 days in an environment with a temperature of 20° C.±3° C. and a relative humidity of more than 90% to obtain modified coral aggregate.

[0120] Compared with Example 1, in this comparative example, the composite powder rust inhibitor and the coating agent are mixed, and then the coral aggregate is soaked and coated.

[0121] According to the standards "Lightweight aggregate and its test methods Part 2: Test methods for lightweight aggregate" (GB / T 17431.2), "Pebble and crushed stone for construction" (GB / T 14685) and "Sand for construction" (GB / T 14684), the cylinder compressive strength, crushing index and free chloride ion content of the modified coral aggregate of the above examples and comparative examples were measured, and compared with the unmodified coral aggregate. The results are shown in Table 1.

[0122] Table 1 Cylinder compression strength, crushing index and free chloride ion content

[0123]

[0124] As can be seen from Table 1, the embodiment of the present invention adopts the method of first absorbing the composite powder rust inhibitor and then modifying the coral aggregate by using a coating agent, so that the pores of the coral aggregate are double-filled, and a coating agent layer is formed on the surface of the aggregate, thereby increasing the pore density and strength of the coral aggregate and significantly solidifying the chloride ions. This composite modification method comprehensively improves the performance of the coral aggregate, so that the modified coral aggregate of the present invention has a cylinder compression strength increased by more than 120% compared with the unmodified coral aggregate, a crushing index reduced by about 19%, and a free chloride ion content reduced by about 70%.

Claims

1. A coral aggregate modifier, comprising at least: The composite powder rust inhibitor, based on the total weight of the composite powder rust inhibitor as 100%, comprises: 30-40% of inorganic salt, 10-30% of carboxylic acid compound and 20-35% of inorganic nanomaterial; wherein the carboxylic acid compound comprises one or a combination of aminocarboxylate and unsaturated carboxylic acid.

2. The coral aggregate modifier according to claim 1, wherein: The inorganic salt includes zinc sulfate and / or calcium sulfate; Preferably, the inorganic salt comprises a combination of zinc sulfate and calcium sulfate, and based on the total weight of the composite powder rust inhibitor being 100%, the content of zinc sulfate is 15-20%, and the content of calcium sulfate is 15-25%.

3. The coral aggregate modifier according to claim 1, wherein: The aminocarboxylate includes aminoacetate, and the unsaturated carboxylic acid includes acrylic acid; Preferably, the inorganic nanomaterial includes nano titanium dioxide and / or nano zinc oxide.

4. The coral aggregate modifier according to claim 1, wherein: Taking the total weight of the composite powder rust inhibitor as 100%, it further comprises: 5-10% of a stabilizer, wherein the stabilizer comprises a surfactant; Preferably, based on the total weight of the composite powder rust inhibitor being 100%, it further comprises: 5-10% of a pH value regulator.

5. The coral aggregate modifier according to claim 1, wherein: The coral aggregate modifier further comprises: a coating agent, wherein the coating agent comprises: cement and water; Preferably, the weight ratio of the composite powder rust inhibitor to the encapsulating agent is (0.2-0.4):

1.

6. The coral aggregate modifier according to claim 5, wherein: The cement includes one or a combination of ordinary cement, special cement and corrosion-resistant cement.

7. The coral aggregate modifier according to claim 5, wherein: The encapsulating agent further comprises: a cementitious material; the weight ratio of the cementitious material to the cement is (0.2-0.4):1; Preferably, the weight ratio of water in the encapsulating agent to the total amount of cement and optionally included cementitious materials is (0.2-0.6):

1.

8. The coral aggregate modifier according to claim 7, wherein: The cementitious material comprises one or a combination of fly ash, blast furnace slag powder, recycled powder, coral sand powder, quartz sand powder and basalt powder.

9. The coral aggregate modifier according to claim 5, wherein: The density of the encapsulating agent is 3.0-3.5 g / cm 3 .

10. A method for modifying coral aggregate, the method using the coral aggregate modifier according to any one of claims 1 to 9, comprising the following steps: (1) soaking the coral aggregate in a solution of the composite powder rust inhibitor to obtain the coral aggregate soaked in the composite powder rust inhibitor; (2) using a coating agent to coat the coral aggregate after being impregnated with the composite powder rust inhibitor to form a coating agent layer, thereby obtaining a coral aggregate having a coating agent layer; (3) Curing the coral aggregate with the coating layer to obtain modified coral aggregate.

11. The method for modifying coral aggregate according to claim 10, wherein: The particle size of the coral aggregate is 5-20 mm.

12. The method for modifying coral aggregate according to claim 10, wherein: The mass fraction of the composite powder rust inhibitor in the composite powder rust inhibitor solution is 3-50%; Preferably, the pH value of the solution of the composite powder rust inhibitor is 9-12; Preferably, the volume ratio of the composite powder rust inhibitor solution to the coral aggregate is (1-3):1; Preferably, the soaking time is 3-5 hours; Preferably, the coral aggregate impregnated with the composite powder rust inhibitor is coated with the coating agent by spraying or immersing under vibration conditions, so that the coating agent is coated on the surface of the coral aggregate and filled in the pores of the coral aggregate, forming a coating agent layer on the surface of the coral aggregate.

13. The method for modifying coral aggregate according to claim 10, wherein: The thickness of the wrapping agent layer is 0.05-0.2 cm.

14. The method for modifying coral aggregate according to claim 10, wherein: The curing includes standard curing, carbonization curing or steam curing; the conditions of the standard curing include: curing for 28 days in an environment with a temperature of 20°C±3°C and a relative humidity of more than 90%; the conditions of the carbonization curing include: curing for 1-28 days in an environment with a carbon dioxide concentration of 20%±3%, a relative humidity of 70%±5% and a temperature of 20°C±2°C; the conditions of the steam curing include: curing for 1-28 days in an environment with a temperature of 50-80°C and a humidity of more than 90%.

15. A modified coral aggregate, prepared by the coral aggregate modification method according to any one of claims 10 to 14.

Citation Information

Patent Citations

  • Corrosion inhibitor mixing method for improving coral concrete structure durability

    CN109354431A

  • Enhancement method of porous coral aggregate

    CN110981255A

  • Nano composite migration type steel bar corrosion inhibitor suitable for concrete in marine environment

    CN112811844A

  • Composite nano particle steel bar corrosion inhibitor and preparation method thereof

    CN114075051A

  • Manufacturing method of seawater coral concrete capable of improving adhesive property

    CN116462456A